Histological Effect of Androgenic Anabolic Steroids on Liver (Indian Journal of Forensic Medicine & Toxicology, 2020)
Abstract: Anabolic androgenic steroids (AAS) they are the synthetic type of the natural male sex hormone(testosterone), they are widespread used amongst athletes to enhance performance. Abuse of AAS is commonamongst players and it is usually accompanied by a many medically based complications. It was reportedthat hepatic problems include cholestasis, elevation of liver enzymes e.g. aminotransferases, as well as,benign hepatic adenomas, jaundice and to less extent of hepatocellular carcinoma was associated with theiruse.A total of (12) adult New Zealand rabbits (Oryctolagus cuniculus) male, aged one year was selected. 2control animals and 10 were treated with injections intramuscularly of the AAS, nandrolone decanoate(15 mg/kg) three times a week for 12 weeks. At the end of experiment the animals were sacrificed and theliver was dissected out and fixed using 10% buffered formalin-saline to prepare blocks for staining withhaematoxylin and eosin for histological examination using the light microscope.The liver of treated animals reveals that there are a mild to severe vascular congestion. There is swelling ofhepatocytes, and inflammatory cell infiltration. Perivascular fibrosis, cellular necrosis was observed in otherslides with sinusoidal congestions and extrabiliary bile pigments deposits.The benefit of AAS comes with unwanted side effects. The total volume of the hepatocytes and sinusoidswere increased in the studied animals. The total number of hepatocytes nuclei in experimental group alsoincreased. The damage of the liver cells or at least increased permeability of the hepatocellular membranewhich is noticed in the present work could explain the increment of plasma levels of liver enzymeswhich was studied by other researchers, as they notice an elevation liver enzymes activity such as alanineaminotransferase (ALT), aspartate aminotransferase (AST), alkaline phosphatase (AP), gamma glutamyltranspeptidase (GGT), and lactate dehydrogenase(LDH)..Patients and physicians must kept in mind that the sequelae of AAS abuse are life threatening. So peopleshould be aware about the complications of AAS use and a periodic examination of liver function and checkout should be done to those treated groups.
Keywords: Androgenic anabolic steroid, histology, liver, liver enzymes.